2018
DOI: 10.3389/fncel.2018.00461
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Taste Bud Cells Utilize Extragemmal 5-Hydroxy-L-Tryptophan to Biosynthesize the Neurotransmitter Serotonin

Abstract: Serotonin or 5-hydroxytryptamine (5-HT) is an important neurotransmitter that is found in mammalian taste buds and can regulate the output of intragemmal signaling networks onto afferent nerve fibers. However, it is unclear how 5-HT is produced, synthesized locally inside taste buds or absorbed from outside sources. In this study, we attempt to address this question by delineating the process of possible 5-HT biosynthesis within taste buds. First, we verified that the rate-limiting enzyme tryptophan hydroxylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The reduction of DDC expression by SARS-CoV2, which results in hampered biosynthesis of the neurotransmitters dopamine and serotonin, provides insight in the cause of the neurological manifestations frequently observed in these patients. In line with this, previous data on the crucial role of DDC-dependent synthesis of serotonin in taste bud cells for normal taste functions [56] might explain the high incidence of smell and/or taste loss in patients [57]. Moreover, serotonin has been shown to exert functions in innate as well as adaptive immunity, [58] thus a putative SARS-CoV-2-mediated deregulation of its production may be extremely beneficial for the virus.…”
Section: Discussionsupporting
confidence: 58%
“…The reduction of DDC expression by SARS-CoV2, which results in hampered biosynthesis of the neurotransmitters dopamine and serotonin, provides insight in the cause of the neurological manifestations frequently observed in these patients. In line with this, previous data on the crucial role of DDC-dependent synthesis of serotonin in taste bud cells for normal taste functions [56] might explain the high incidence of smell and/or taste loss in patients [57]. Moreover, serotonin has been shown to exert functions in innate as well as adaptive immunity, [58] thus a putative SARS-CoV-2-mediated deregulation of its production may be extremely beneficial for the virus.…”
Section: Discussionsupporting
confidence: 58%
“…13 ACE2 and DDC are expressed by murine taste buds 14 and the DDC-dependent synthesis of serotonin was found to be mandatory for normal taste functions. 15 Besides the hypothesis of a cytopathic effect on neurosensory cells, the high incidence of smell and/or taste loss in COVID-19 patients might thus reflect the impact of SARS-Cov2 on the synthesis of neurotransmitters (notably serotonin and dopamine) by ACE2expressing cells.…”
Section: Causes Of Hypogeusia/hyposmia In Sars-cov2 Infected Patientsmentioning
confidence: 99%
“…Currently, among the five basic tastes, sweet, umami, and bitter are thought to be accepted by type II, sour by type III, and salty by type III. Type III taste cells synapse with taste nerve fibers expressing serotonin receptors, and express aromatic Lamino acid decarboxylase (AroDC) [7], which catalyzes the production of serotonin [8]. Some previous studies have suggested that serotonin released from taste buds activates serotonin receptors on taste nerve fibers to facilitate taste signaling [9,10].…”
Section: Introductionmentioning
confidence: 99%